First record of the invasion of dendrocephalus brasiliensis pesta, 1921 (Crustacea: Anostraca: Thamnocephalidae) in são paulo state, Brazil - Mai, Mônica G.; Silva, Talita A. S. [UNESP]; Almeida, Viviane L. S.; Serafini, Raphael L. (My University, 2008)
This is the first record of invasion of the Dendrocephalus brasiliensis in São Paulo State, Brazil. It also is a review of previous studies of this species and discusses the importance of this microcrustacean as feed for aquaculture, as well as the risks of its invasion in new habitats.
Keywords: Alien species; Aquaculture; Branchoneta; Branconeta; Ornamental fisheries